Galectin-1 Prevents Infection and Damage Induced by Trypanosoma cruzi on Cardiac Cells. - Alejandro F Benatar; Gabriela A García; Jacqeline Bua; Juan P Cerliani; Miriam Postan; Laura M Tasso; Jorge Scaglione; Juan C Stupirski; Marta A Toscano; Gabriel A Rabinovich; Karina A Gómez (Public Library of Science (PLoS), 2015)
BACKGROUND:Chronic Chagas cardiomyopathy caused by Trypanosoma cruzi is the result of a pathologic process starting during the acute phase of parasite infection. Among different factors, the specific recognition of glycan structures by glycan-binding proteins from the parasite or from the mammalian host cells may play a critical role in the evolution of the infection. METHODOLOGY AND PRINCIPAL FINDINGS:Here we investigated the contribution of galectin-1 (Gal-1), an endogenous glycan-binding protein abundantly expressed in human and mouse heart, to the pathophysiology of T. cruzi infection, particularly in the context of cardiac pathology. We found that exposure of HL-1 cardiac cells to Gal-1 reduced the percentage of infection by two different T. cruzi strains, Tulahuén (TcVI) and Brazil (TcI). In addition, Gal-1 prevented exposure of phosphatidylserine and early events in the apoptotic program by parasite infection on HL-1 cells. These effects were not mediated by direct interaction with the parasite surface, suggesting that Gal-1 may act through binding to host cells. Moreover, we also observed that T. cruzi infection altered the glycophenotype of cardiac cells, reducing binding of exogenous Gal-1 to the cell surface. Consistent with these data, Gal-1 deficient (Lgals1-/-) mice showed increased parasitemia, reduced signs of inflammation in heart and skeletal muscle tissues, and lower survival rates as compared to wild-type (WT) mice in response to intraperitoneal infection with T. cruzi Tulahuén strain. CONCLUSION/SIGNIFICANCE:Our results indicate that Gal-1 modulates T. cruzi infection of cardiac cells, highlighting the relevance of galectins and their ligands as regulators of host-parasite interactions.